Fast dual‐doppler LiDAR retrieval of boundary layer wind profiles. (26th June 2020) - Ng, C.W.; Hon, K.K.
Abstract : Operational doppler LiDARs (light detection and ranging) are often heavily engaged in specialised phenomenon detection, as well as dedicated surveillance scans, leaving little room for further additions to the tightly packed scanning strategy. This paper presents a fast method for retrieval of the urban boundary layer wind profile using existing scan data from two long‐range doppler LiDARs at the Hong Kong International Airport (HKIA). Leveraging occasional range height indicator scans originally designed to aid the monitoring of terrain‐induced wind disturbances, vertical profiles of the horizontal winds between 150 and 750m above ground level are estimated near the intersection point. The LiDAR‐derived wind profiles are validated against measurements from a nearby wind profiler, as well as Aircraft Meteorological Data Relay (AMDAR) flight observations, for a 1‐year period, 2019. Results indicated close agreement in terms of wind speed and direction between the LiDAR‐derived profiles and wind profiler measurements, particularly above 300m. A slant angle correction factor is found to effectively alleviate the underestimation of the horizontal wind components at higher beam angles while also improving the consistency of the retrieved wind speed profile across different altitudes. For the AMDAR comparison, large discrepancies in wind speed and direction might be attributed to the natural variability of glide path winds well‐known to HKIA. This study demonstrates the potential of extracting additional boundary layer wind information from 'part‐time' scans of operational doppler LiDARs.